Pengaruh Pembelajaran Motorik Dasar terhadap Koordinasi Gerak Siswa SDN 4 Lando - Ramdani Setiawan (Journal of Elementary Education Research, 2025)
This descriptive qualitative literature review explores the impact of fundamental motor skill (FMS) learning on students’ movement coordination abilities at the elementary school level, with specific relevance to SDN 4 Lando. Fundamental motor skills—such as locomotor, non-locomotor, and manipulative movements—serve as the foundation for children’s physical development and future participation in various physical activities and sports. The purpose of this study is to analyze how structured FMS instruction contributes to improvements in balance, rhythm, accuracy, body control, and overall coordination. The data were collected through an in-depth review of academic sources, including scientific journals, books, and conference proceedings indexed in Google Scholar. A thematic content analysis was used to identify recurring patterns, concepts, and research findings. The results show that well-designed FMS programs significantly enhance students’ motor coordination, increase motivation in physical activities, and improve cognitive engagement during learning. Studies also highlight the importance of varied activities such as obstacle courses, ball-handling drills, rhythmic movements, and cooperative games that stimulate bilateral coordination and body awareness. In conclusion, fundamental motor skill instruction plays a crucial role in shaping children’s psychomotor development, serving as a pathway toward improved physical literacy and long-term participation in healthy physical activity.